2018
DOI: 10.3390/su10020552
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of Regional Discrepancies in Carbon Emissions from Agricultural Land Utilization: Evidence from Chinese Provincial Data

Abstract: Agricultural land, as an important carbon source, has produced about 20% of carbon dioxide globally. The calculation and spatial-temporal distribution of carbon emissions resulting from agricultural land utilization (ALU) has attracted a great deal of attention from scholars. Most of the existing literature widely agrees that China's carbon emissions from ALU showed significant regional discrepancies, but rarely pays attention to the evolutionary characteristics of the discrepancies. This study calculated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Gerlagh applied the endogenous technological progress model to study the influence of technological progress on carbon emission reduction [18] and confirmed that technological progress significantly reduced the cost of carbon emission reduction through the learning effect and increased the social benefits at the same time. Furthermore, agricultural land also affects the agricultural carbon emissions, such as per capita land use area [19], agricultural land use [20] and farmland conversion [21,22]. Besides, there also exists a close relationship between agricultural income and carbon emissions [23].…”
Section: Influencing Factors Of Agricultural Carbon Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerlagh applied the endogenous technological progress model to study the influence of technological progress on carbon emission reduction [18] and confirmed that technological progress significantly reduced the cost of carbon emission reduction through the learning effect and increased the social benefits at the same time. Furthermore, agricultural land also affects the agricultural carbon emissions, such as per capita land use area [19], agricultural land use [20] and farmland conversion [21,22]. Besides, there also exists a close relationship between agricultural income and carbon emissions [23].…”
Section: Influencing Factors Of Agricultural Carbon Emissionsmentioning
confidence: 99%
“…According to the IPCC guidelines, on the basis of the existing research about the carbon emission equation [20,28,29,36], in view of the current situation of agricultural development in Fujian Province, this paper chooses carbon emission sources and corresponding carbon emission coefficients to build a model for calculating agricultural carbon emissions. The specific formula is as follows:…”
Section: Estimation Of Agricultural Carbon Emissionsmentioning
confidence: 99%
“…The carbon dynamics caused by LULCC could be investigated through the division of different land use/land cover types, and carbon emission effects of different land use/land cover types could thus be accurately explored 23 . However, previous studies were mainly focused on carbon emissions taking place on a single land-use type, such as carbon emissions resulting from agricultural land utilization 24 or built-up land construction 25 , neglecting to establish the whole carbon estimation system based on land use/land cover 23 . Furthermore, a comprehensive comparison between carbon emissions and carbon sinks of land use/land cover remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, these processes are coupled with carbon emissions, albeit mainly in an indirect way. According to existing studies [17,45,46], carbon emissions from agricultural production activities in this study mainly include (1) the carbon emissions generated from the production and usage of fertilizers, pesticides, and agricultural plastic films; (2) the carbon emissions generated by direct or indirect consumption of fossil fuels (mainly agricultural diesel) due to the use of agricultural machinery; (3) the loss of soil organic carbon due to agricultural tillage; and (4) the carbon emissions from fossil fuels consumed by electrical energy used in the agricultural irrigation process.…”
Section: Carbon Emissions Of Croplandmentioning
confidence: 99%
“…Previous studies have mainly focused on carbon emissions taking place on a single land use type, such as emissions from agricultural land [17] or built-up land [18]. A comprehensive carbon emissions estimation system based on land use remains poorly documented at the provincial level in China.…”
Section: Introductionmentioning
confidence: 99%